Analisis Pengaruh Belanja Bantuan sosial, Pendidikan dan Tingkat Pengangguran Terhadap Kemiskinan di Provinsi Jawa Timur Tahun 2018 - Ayu, Dyah Puspitaning; prabowo, prayudi setiawan (Independent: Journal of Economics, 2021)
The purpose of this study is to determine the effect of spending on social assistance, education and unemployment on poverty in East Java in 2018.This study uses crosssectional data analysis techniques of 38 districts/towns obtained from the Central Bureau of Statistics and then processed with multiple linear regression. The results of the study show that partially spending on social assistance had a significant positive effect on poverty in East Java province in 2018, education had a significant negative impact on poverty in East Java in 2018, and the unemployment rate did not significantly affect poverty in East Java in 2018. Meanwhile, spending on social aid and education simultaneously affected poverty in East Java province in 2018. Keywords: education, poverty, sosial insurrence, unemployment